The Final Bet; A Novel - Hamdouchi, Abdelilah; Translated by Smolin, Jonathan (New York Hoopoe, 2016)
Casablanca. Othman, a handsome young Moroccan man, returns home to discover his elderly French wife, Sofia, brutally murdered in their bedroom. Highly educated but chronically unemployed, Othman had been in desperate straits before meeting Sofia, who pampered him with fancy cars, expensive clothes, and access to her mansion in the most exclusive neighborhood in Casablanca. But living with a woman more than forty years his senior was too much for Othman before his wife's murder he sought relief in a steamy affair with an attractive young aerobics instructor, Naeema. The Moroccan police quickly zero in on Othman as the prime suspect in his wife's murder. But is he guilty? Did he kill his wife for the money and his lover? Or is he an innocent man, framed by circumstance and an overzealous and brutal police force? Abdelilah Hamdouchi's The Final Bet is the first Arabic detective novel to be translated into English. With it, Hamdouchi joins the ranks of Yasmina Khadra and Henning Mankell, finally bringing the modern Arabic novel to the global stage of detective fiction.
Keywords: Murder -- Police -- Morocco--Casablanca -- Detective and mystery stories